The Role of Islamic Religious Education for the Character of Youth in Association - Arli Marlina; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Islamic religious education is very important for character building, especially in socializing the community. In today's era students tend to not care about society, therefore forming a good character is very important, especially in social society. Islamic religious education itself teaches that we are required to have good character according to what was taught by the Prophet Muhammad SAW; Allah SWT says, which means "and verily you (Muhammad) have a noble character". Because of that, it can be concluded that the Prophet Muhammad, was sent to earth to improve the character of all human beings. Thus, the character of education from an Islamic point of view is needed, especially in Islamic educational institutions. So, from various problems related to morals, which ideally can realize character education, especially in a social society in an Islamic perspective in the form of caring for others. courtesy towards parents. sense of responsibility and care for fellow human beings.